A New Insight Into Amicula, a Genus of Tiny Marine Benthic Diatoms With the Description of Two New Tropical Species and the Largest Mitogenome Known for a Stramenopile - Gastineau, Romain; Li, Chunlian; Ashworth, Matt P.; Witkowski, Andrzej; Turmel, Monique; Górecka, Ewa; Frankovich, Thomas A.; Wachnicka, Anna; Lobban, Christopher S.; Theriot, Edward C.; Otis, Christian; Dąbek, Przemysław; et al. (Frontiers in Marine Science, 2022)
The current article focuses on the morphological and molecular characterization of the often inconspicuous genus Amicula. This recently erected genus from brackish and marine sediments was monotypic but here we describe two new tropical species: Amicula micronesica sp. nov. and Amicula vermiculata sp. nov. Once considered an incertae sedis genus regarding its higher rank taxonomy, its position among the family Diploneidaceae is proposed here by molecular phylogenetics. The complete plastid and mitochondrial genomes of Amicula micronesica sp. nov. are also presented here. It appears that the 177614-bp long mitogenome is the biggest yet recorded among stramenopiles, due to its invasion by 57 introns. Moreover, it utilizes the genetic code 4 for translation instead of the code 1 usually found among diatoms.